A Retrospective Study of Custodial Deaths in Chhattisgarh Region - Bansal, SJ; Jaiswani , AK; Manjhi, SN; Dengani , M (Journal of Indian Academy of Forensic Medicine, 2024)
The death of a person in custody has always been in the limelight. Some people in custody die because of some form of violence, some due to accidents and some because of natural disease. In this study, we have attempted to identify the various causes of death in a person under custody in the Chhattisgarh region. A single-centre, retrospective study was conducted for all cases (n=35) of custodial death between the years 2018 and 2019. Data collected included age, sex, manner of death, place of death and cause of death. Male inmates have a higher rate of custodial deaths. 100 % of male and 90 % of female deaths in custody are natural deaths. The most affected age group was the 51-60- year age group. The hospital was the place of death for 100 % of males and 90 % of females. Tuberculosis and cirrhosis of the liver were among the common causes of death in a person in custody. Deaths in custody in Chhattisgarh are primarily natural deaths. Regular health screening and proper health care facilities for the prisoners are the need of the hour.